2012
DOI: 10.1007/s00280-012-2031-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the long-term pharmacokinetics of bevacizumab following last dose in patients with resected stage II and III carcinoma of the colon

Abstract: Long-term bevacizumab PK in this study was predictable based on short-term PK data from metastatic settings in other tumor types. An exploratory analysis demonstrated no apparent association of the tested covariates with bevacizumab PK. Further, the extended serum persistence of bevacizumab following last dose should be considered in clinical study designs and post-treatment evaluations that may be affected by bevacizumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…Bevacizumab pharmacokinetics is well established in phase-I, -II, and -III studies as a single agent or in combination with chemotherapy for both single- and multiple-dose administration with both rich and sparse bevacizumab serum concentration data (1417). Bevacizumab pharmacokinetics showed dose linearity within the dose range of 1–20 mg/kg, a slow clearance, a volume of distribution consistent with limited extravascular distribution, and a terminal half life of approximately 20 days.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bevacizumab pharmacokinetics is well established in phase-I, -II, and -III studies as a single agent or in combination with chemotherapy for both single- and multiple-dose administration with both rich and sparse bevacizumab serum concentration data (1417). Bevacizumab pharmacokinetics showed dose linearity within the dose range of 1–20 mg/kg, a slow clearance, a volume of distribution consistent with limited extravascular distribution, and a terminal half life of approximately 20 days.…”
Section: Introductionmentioning
confidence: 99%
“…Bevacizumab pharmacokinetics showed dose linearity within the dose range of 1–20 mg/kg, a slow clearance, a volume of distribution consistent with limited extravascular distribution, and a terminal half life of approximately 20 days. Short-term ( e.g ., up to 30 days after dose) and long-term (up to 6 months after dose) pharmacokinetics of bevacizumab is comparable (17). A population pharmacokinetic model has been previously established in metastatic colorectal, breast, non-small cell lung, and prostate cancer, and showed that bevacizumab pharmacokinetics is consistent across these cancers (15).…”
Section: Introductionmentioning
confidence: 99%
“…A long-term pharmacokinetics study demonstrated extended serum persistence of bevacizumab following termination of bevacizumab 3 and 6 months after the last administration, which may affect clinical outcomes of post-bevacizumab treatment (12). This prompted us to investigate the impact of shorter intervals between bevacizumab and anti-EGFR therapy on the efficacy of subsequent anti-EGFR therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The results of previous reports also support our findings. We speculated that a BFI cutoff of 6 months is an efficient scale for evaluating the interaction between bevacizumab and anti-EGFR antibodies, because previous reports demonstrated that bevacizumab was detected in plasma at 6 months after the last administration [27]. CAIRO2 and PACCE, two previous prospective studies that evaluated the efficacy of bevacizumab and anti-EGFR antibodies combination therapy, failed to show a survival benefit [28,29].…”
Section: Discussionmentioning
confidence: 99%